2020
DOI: 10.1177/0972652720969519
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Yield Spread Between Sukuk and Conventional Bonds in Malaysia

Abstract: This article aims to shed light on the differences in yield rate between conventional bond and sukuk in the Malaysian market. We find that the historical yield rates for the government-issued sukuk is significantly higher than the conventional bond. Conversely, there is a slight yield spread discount between the corporate-issued sukuk and bonds for all rating classes. We conclude that liquidity factor can mainly explain the positive yield spread on the government-issued sukuk. We also illustrate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…All of these factors suggest that liquidity conditions in the sukuk market are likely to be less favourable than those observed in similar conventional bonds market, thus providing a strong support for our empirical findings. This is also backed by the empirical results from Asmuni and Tan (2021) who document the presence of some form of liquidity premium in the pricing of Malaysian sovereign sukuk issuances.…”
Section: Revisiting the Question Of Liquiditymentioning
confidence: 77%
See 3 more Smart Citations
“…All of these factors suggest that liquidity conditions in the sukuk market are likely to be less favourable than those observed in similar conventional bonds market, thus providing a strong support for our empirical findings. This is also backed by the empirical results from Asmuni and Tan (2021) who document the presence of some form of liquidity premium in the pricing of Malaysian sovereign sukuk issuances.…”
Section: Revisiting the Question Of Liquiditymentioning
confidence: 77%
“…The current body of literature suffers from several limitations. First, all of the past studies had very limited scope with majority focusing on comparing liquidity conditions of sukuk and bonds in a specific domestic market and the remaining studies focusing on limited international issuances (Alabbasi et al , 2021; Ariyana et al , 2020; Asmuni and Tan, 2021; Hameed et al , 2019; Nienhaus and Karatas, 2016). This has significantly limited the relevance of such findings to other domestic and international markets.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the standard deviation of public expectations regarding inflation rates can be a strong explanatory variable for the emergence of noise in the Turkish bond market. Asmuni and Tan (2021) investigated the yield differences between sukuk and conventional bonds in the domestic market of Malaysia. The study indicated that historically, government-issued Sharia bonds have higher yields than conventional bonds, while for sukuk or bonds issued by corporations, the yield differential is not clear.…”
Section: Introductionmentioning
confidence: 99%